Role of the nurse in the management of postpartum hemorrhages: A literature review (Research, Society and Development, 2024)
Objective: To thoroughly analyze the role of nurses in managing postpartum hemorrhage, focusing on the skills necessary for the prevention, early detection, and treatment of this obstetric complication, which remains one of the leading causes of maternal morbidity and mortality worldwide. Materials and Methods: This is an integrative literature review covering studies published between 2019 and 2023 in the Scielo, Lilacs, and PubMed databases, using specific descriptors related to the topic. The analysis of the studies revealed that effective prevention of postpartum hemorrhage requires early identification of risk factors during prenatal care, a critical role performed by nurses, who must also provide detailed educational information to pregnant women. Results: The importance of continuous training and evidence-based protocol updates was emphasized to ensure intervention effectiveness and care safety. The results highlight the need for an interdisciplinary approach in postpartum care, underscoring the central role of nurses in coordinating care and providing psychosocial support. The research also identified the relevance of health policies promoting continuous training of nursing professionals and adherence to updated clinical protocols. Final considerations: In conclusion, this study contributes to raising awareness about the importance of evidence-based practices and health policies that strengthen obstetric nursing practices, offering guidelines to improve postpartum hemorrhage management and, consequently, reduce maternal mortality.